(untitled) (Journal of the College of Basic Education, 2023)
One of the important topics that preoccupied grammatical thought, past and present, is the question of time, its connotations and how it is. Time is one of the effective and influential topics in grammatical thought because it has many temporal dimensions. Semitic or from other linguistic blasts. The context also has a significant impact on defining time in the linguistic text of tools, verbs, the position and the context of the case represented by the causes of revelation and the addressee and its transitions.